Brain activity and the production of written text during mediumistic trance: A controlled EEG study - Kleber Monteiro Pinto; Thaise G. L. de O. Toutain; Hugo Saba; Marco Aurélio Vinhosa Bastos Jr; Raphael Silva do Rosário; Jéssica Plácido; Naíma Loureiro; Valéria C. Fernandes; José Garcia Vivas Miranda (PLoS ONE, 2026)
Mediumistic trance, studied as a cultural phenomenon, is considered an altered state of consciousness with dissociative and non-pathological characteristics. Studies on the effect of this trance state on linguistic performance using electroencephalography (EEG) are still scarce. We investigated the brain electrical activity of mediums using quantitative EEG (qEEG) during writing in waking and trance, and compared them with a matched control group performing simulated mediumistic writing and waking writing (n = 9 per group). EEG power differences exhibited increases across theta, alpha, beta1, and beta2 bands (p < .05) distinguishing activity during trance writing from the simulated mediumistic writing conditions. For the textual evaluations, within-group analyses showed that mediums’ trance texts scored higher than their waking texts. In contrast, no significant intergroup differences in overall text quality emerged between mediums and controls. Together, these findings support the view that complex linguistic production is preserved across groups, while trance is associated with distinct spectral dynamics during writing in the mediums’ group. Further research is warranted to refine the characterization of neural patterns supporting linguistic production in altered states of consciousness.